Analysis shariah of gold investment account : study at Kuwait Finance House Malaysia Berhad / Mohd Fikrieddin Baharom - Baharom, Mohd Fikrieddin (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Gold investment accounts are safe and easy gold investment portfolios, where gold purchased by investors will be kept by banks. In Malaysia, there are 6 banks offering gold investment accounts but only KFHMB are Shariah compliant. Therefore, the study was conducted at KFHMB. This study reviews the implementation of the gold investment account carried out at KFHMB and analyse it in terms of shariah compliance. Data and information obtained through documentation and interviewing methods with KFHMB officer, then analysed using the comparative method of comparison between the implementation of KFHMB with contract of As-Sarf and AlQard. The findings show that the overall implementations of KFHMB gold investment account are shariah compliant.